Case Study Analysis as an Effective Teaching Strategy: Perceptions of Undergraduate Nursing Students From a Middle Eastern Country. (November 2021) - Seshan, Vidya; Matua, Gerald Amandu; Raghavan, Divya; Arulappan, Judie; Al Hashmi, Iman; Roach, Erna Judith; Sunderraj, Sheeba Elizebath; Prince, Emi John
Background: Case study analysis is an active, problem-based, student-centered, teacher-facilitated teaching strategy preferred in undergraduate programs as they help the students in developing critical thinking skills.Objective: It determined the effectiveness of case study analysis as an effective teacher-facilitated strategy in an undergraduate nursing program.Methodology: A descriptive qualitative research design using focus group discussion method guided the study. The sample included undergraduate nursing students enrolled in the Maternal Health Nursing Course during the Academic Years 2017 and 2018. The researcher used a purposive sampling technique and a total of 22 students participated in the study, through five (5) focus groups, with each focus group comprising between four to six nursing students.Results: In total, nine subthemes emerged from the three themes. The themes were "Knowledge development", "Critical thinking and Problem solving", and "Communication and Collaboration". Regarding "Knowledge development", the students perceived case study analysis method as contributing toward deeper understanding of the course content thereby helping to reduce the gap between theory and practice especially during clinical placement. The "Enhanced critical thinking ability" on the other hand implies that case study analysis increased student's ability to think critically and aroused problem-solving interest in the learners. The "Communication and Collaboration" theme implies that case study analysis allowed students to share their views, opinions, and experiences with others and this enabled them to communicate better with others and to respect other's ideas which further enhanced their team building capacities.Conclusion: This method is effective for imparting professional knowledge and skills in undergraduate nursing education and it results in deeper level of learning and helps in the application of theoretical knowledge into clinical practice. It also broadened students' perspectives, improved their cooperation capacity and their communication with each other. Finally, it enhanced student's judgment and critical thinking skills which is key for their success.